The Effect of Political Connection, Independent Commissioners And Sales Growth On Earning Management with Company Size as A Moderating Variable - Maria Djojo, Venia; Dwi Astuti, Christina (Devotion : Journal of Research and Community Service, 2023)
The purpose of this research is to analyze the effect of Political Connection, Independent Commissioner, sales growth on earnings management. The population of this research is all manufacturing companies in the consumer industry sector that are listed on the Indonesia Stock Exchange from 2018 to 2021. There are 31 companies that meet the criteria using the purposive sampling method. The results show that sales growth have a positive effect on earnings management. Political connections and independent commissioners have no effect on earnings management. The moderating variable of company size is able to strengthen the effect of sales growth on earnings management but is unable to strengthen the influence of political connections and independent commissioners on earnings management.